2016
DOI: 10.1007/s40429-016-0108-9
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Disorder and Minority Populations: Prevalence and Risk Factors

Abstract: Purpose of review Previous studies demonstrate disparities in health and health services including gambling disorders (GD) among ethnic and racial minority groups. In this review, we summarize studies examining the prevalence of GD across different ethnic and racial minorities. Recent findings We describe the sociodemographic subgroup variations at heightened risk for GD and factors associated with GD in racial and ethnic minority groups including gambling availability, comorbid substance use, psychiatric co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 57 publications
1
35
1
1
Order By: Relevance
“…24 Some population subgroups, such as Native Americans and blacks, and alcohol abusers have higher rates of gambling involvement than others in the population. 32 In this national U.S. sample, not only do Native Americans and blacks have higher rates of problem gambling than whites, but some risk factors have a greater impact on gambling involvement for Native Americans and blacks than they do for whites. In each level of gambling involvement, the relationships between gambling and neighborhood disadvantage are stronger for Native Americans than for other population groups.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…24 Some population subgroups, such as Native Americans and blacks, and alcohol abusers have higher rates of gambling involvement than others in the population. 32 In this national U.S. sample, not only do Native Americans and blacks have higher rates of problem gambling than whites, but some risk factors have a greater impact on gambling involvement for Native Americans and blacks than they do for whites. In each level of gambling involvement, the relationships between gambling and neighborhood disadvantage are stronger for Native Americans than for other population groups.…”
Section: Discussionmentioning
confidence: 86%
“…11, 32 The main effects’ odds ratios are the largest of any other variables after controlling for all other demographic and individual factors. This consistent finding supports the long-standing notion that problem gambling and substance abuse are part of a common problem behavior syndrome.…”
Section: Discussionmentioning
confidence: 91%
“…In the United States, Native Americans, Asians, and blacks show a greater prevalence of GD compared with whites . These findings are similar to those found in aboriginal groups in other countries, including Canada, Greenland, and Australia . Risk factors for GD, such as socioeconomic disadvantage and a higher prevalence of psychiatric disorders, including SUDs, are more prominent in certain ethnic and racial groups.…”
Section: Risk Factorsmentioning
confidence: 99%
“…29 These findings are similar to those found in aboriginal groups in other countries, including Canada, Greenland, and Australia. 19 Risk factors for GD, such as socioeconomic disadvantage and a higher prevalence of psychiatric disorders, including SUDs, are more prominent in certain ethnic and racial groups. Beliefs, values, gambling availability, and cultural acceptability toward gambling also vary in different parts of the world.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Studies have shown that being foreign born and belonging to an ethnic minority may constitute a risk factor for problem gambling ( Alegría et al, 2009 ; Caler, Vargas Garcia, & Nower, 2017 ; Canale et al, 2017 ; Giralt et al, 2018 ; James, O'Malley, & Tunney, 2016 ; Lyk-Jensen, 2010 ; Okuda et al, 2016 ; Welte et al, 2004 ; Wilson, Salas-Wright, Vaughn, & Maynard, 2015 ). However, authors have suggested that ethnicity may not be a risk factor in itself, but associated risk factors are likely to mediate the increased risk ( Kastirke, Rumpf, John, Bischof, & Meyer, 2015 ; Okuda et al, 2016 ), and this includes the finding that immigrants may present a more severe gambling pattern, compared to natives ( Eva et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%